Stable carbon and nitrogen isotope ratios of surface food residues in pre-Columbian ceramics from the southern Pacific of Costa Rica as evidence of prehistoric human diets (UNED Research Journal, 2019)
Introduction: to understand and interpret the consumption of plants and animals by humans in the past requires the investigation of different lines of evidence. Identifiable macroscopic remains of plants and animals, for example seeds and bones, are frequently found at archaeological sites and provide key data on food resources. Their analysis is complemented by the study of pollen grains or phytoliths of cultivated plants within archaeological horizons or in sediment cores recovered from lakes and wetlands near archaeological sites. Another important source of information on human diets in the past consists of food residues preserved in or on artefacts excavated from archaeological sites. Objective: to examine food residues in archaeological pottery from coastal and interior sites in the southern Pacific region of Costa Rica. Methods: we focus on isotopic analysis of carbonized food residues preserved on the inner surfaces of ceramic pots, plates, and other ceramic pieces from archaeological excavations in the intermediate zone (elevations 500-1500m) and coastal zone of the southern Pacific region of Costa Rica. Isotopic analysis of surface food residues on pottery relies on the fact that stable isotopes of carbon (12C and 13C) and nitrogen (14N and 15N) in foods differ based on the photosynthetic pathway of plants and on trophic level. Results: in our analysis of material from twelve sites we found evidence of diets with high amounts of C4 plants (likely maize), legumes, herbivores, and mixtures, but we did not find robust evidence of food residues with isotopic signatures characteristic of reef animals and mollusks, even though some sites are shell mounds. Conclusion: our research represents one of the first studies of surface food residues from Costa Rican pottery, and indicates the potential for studies of this type to strengthen understanding of indigenous subsistence patterns through time and across Costa Rican archaeological regions.
Keywords: Archaeology; food residues; maize; prehistoric diets; pottery; stable isotopes; southern Pacific Costa Rica